STRATEGY OF ENHANCING OF COMPETITIVENESS OF THE AGRO-INDUSTRIAL COMPLEX OF VOJVODINA - CONTROVERSIES, LIMITATIONS, SOLUTIONS - Sofija ADZIĆ (Journal of Central European Agriculture, 2009)
The paper treats the problem of low competitiveness of agro-industrial complex of Vojvodina primarily as the internal phenomenon. In this context, a form of neo-liberal concept of the Strategy of enhancing of competitiveness of agroindustrial complex of Vojvodina is proposed. The basis of the strategy is enhancing of competitiveness of the total agro-industrial superstructure in compliance with the open market economy criteria. According to that the following has been analysed: (1) “How to develop (regional) social-economic environment that will act as a stimulus for enhancing of economic efficiency of the total agrarian production and competitiveness of family farms and companies within the agro-industrial complex?” (2) “How to overcome the internal and external barriers at the level of financing of the current and extended reproduction in a neo-liberal environment of strict monetary restrictions?” and (3) “How to create economically sustainable family farms)?”.